Dilemmas in providing humanitarian intervention in ethnic conflict: a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies - Haddon, Matthew Perry (Massey University, 2004)
This thesis explores the difficulties of providing humanitarian assistance in ethnic conflict situations, explaining the problems and offering suggestions to mitigate the consequences. Ethnic conflicts are complex situations that result from and exacerbate uneven development, political instability, social inequality and poverty. Humanitarian intervention has evolved to become as complex as the conflict itself. Humanitarian agencies are increasing in number and diversification, expanding their capacity to address emergency situations. As a consequence, the repercussions of assistance have also increased and the exploitation of aid by warring parties and the creation of dependency have become central concerns. The commitment of political institutions is important for the success of humanitarian intervention yet it often remains in doubt. Unwillingness to be involved in the problems of another state or region has minimal appeal where no national security issues are at stake. The tendency to misinterpret or obfuscate the causes and processes of conflict has compromised the capability of political actors to address the conflict and its consequences. The conflicts in Rwanda, Bosnia and the Solomon Islands illustrated the multifarious problems associated with humanitarian assistance and the subsequent consequences. It is suggested the capability of humanitarian intervention in the future relies on its re-evaluation in an effort to deal with the specific aspects of the given conflict and minimise the inappropriate allocation of aid. Furthermore, reform of the processes of development in conflict and post-conflict situations is required in an effort to bolster the resilience of recipient populations to the processes conducive to conflict. The support and commitment from political actors also remains critical for the success of humanitarian intervention. The need for early assessment and pre-emptive or reconciliatory diplomacy are key objectives yet must be backed by military capabilities necessary for the protection of the providers and the beneficiaries of relief aid.
Keywords: Humanitarian intervention; Humanitarian assistance; Political aspects; Case studies; Ethnic conflict